Developing Argumentative Essay Writing Skills among Junior High School Students through a Writing Conference using the Toulmin Model - Baylon, Margie F. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol 2 No 2 (2024): Philippine Journal of Education Studies, 2025)
Writing is an essential skill in language production that requires practice and proficiency. This paper describes how writing conferences using the Toulmin model improved the argumentative writing performance of Junior High School students (n=20) in an Integrated High School. Following a mixed- method design, qualitative and quantitative data were collected through pre- writing and post-writing activities. The t-test p-value was used to interpret the quantitative data. Meanwhile, open-ended questions and inter-rater comments examined how writing conferences helped students improve their writing. A rubric was used to grade the participants’ written output while thematic analysis was utilized to extract meaningful themes from the participant’s responses. The findings indicate that writing conferences using the Toulmin Model significantly improved the argument structure and writing quality of students’ papers, as evidenced by significant differences in the mean scores between the participants’ pre-writing and post-writing activities. The formulated themes include constructing claims/arguments, presenting/ gathering evidence, expressing ideas, centering on the topic, and reliability and truthfulness of resources. These findings shed light on the vital role that writing plays in overall communication as it improves other language skills like speaking and reading. Finally, it was found that argumentative essays helped students develop their critical thinking skills and defend their viewpoints with evidence which is essential to other language skills.